2017
DOI: 10.3899/jrheum.161128
|View full text |Cite
|
Sign up to set email alerts
|

Urine Biomarkers to Predict Response to Lupus Nephritis Therapy in Children and Young Adults

Abstract: Low urine levels of TGF-β and ceruloplasmin at baseline and marked reduction of AGP, LPGDS, transferrin, or VDBP and combinations of other select biomarkers by Month 3 are outstanding predictors for achieving remission of LN. If confirmed, these results can be used to help personalize LN therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…Given the complexity of the pathogenesis of lupus nephritis, it is now widely accepted that a single urinary biomarker might not be powerful enough. Many groups have tried different approaches to address this [ 36 , 38 , 43 45 ]. In this study, we used a multiplex technology to simultaneously measure 10 candidate UBMs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity of the pathogenesis of lupus nephritis, it is now widely accepted that a single urinary biomarker might not be powerful enough. Many groups have tried different approaches to address this [ 36 , 38 , 43 45 ]. In this study, we used a multiplex technology to simultaneously measure 10 candidate UBMs.…”
Section: Discussionmentioning
confidence: 99%
“…p values < 0.05 from 2-sided testing were considered statistically significant. To predict renal functional decline up to 12-months post baseline, urinary biomarker levels were tested in mixed model analyses as described previously [14]. Excel 2013 (Microsoft, Redmond, WA) and SAS 9.4 (SAS Institute, Cary, NC) programs were used for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…At each visit, the systemic lupus erythematosus (SLE) disease activity index (SLEDAI-2 K) was completed, with additional calculation of its renal domain score (renal-SLEDAI; range, 0 to 16; 0 = no LN activity) as well as the renal domain score of the Systemic Lupus International Collaborating Clinics/ American College of Rheumatology damage index (renal- SDI; range, 0 to 3; 0 = no LN damage) [14, 32]. Laboratory data recorded included serum creatinine, urine sediment, urine protein to creatinine ratio (UPCR) from a random spot urine sample, and the estimated glomerular filtration rate (GFR), using the modified Schwartz formula [33].…”
Section: Methodsmentioning
confidence: 99%
“…More recently, it has been reported that serum level of L-PGDS may represent a biomarker of kidney function ( White et al, 2015 ), pregnancy-induced hypertension ( Duan et al, 2016 ), and active lupus nephritis ( Brunner et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%